A Systematic Review of Acquired Uterine Arteriovenous Malformations: Pathophysiology, Diagnosis, and Transcatheter Treatment - Daniel J. Yoon; Megan Jones; Jamal Al Taani; Catalin Buhimschi; Joshua D. Dowell (Thieme Medical Publishers, Inc., 2016)
Abstract Objective An acquired uterine arteriovenous malformation (AVM) is a rare cause of vaginal bleeding and, although hysterectomy is the definitive therapy, transcatheter embolization (TCE) provides an alternative treatment option. This systematic review presents the indications, technique, and outcomes for transcatheter treatment of the acquired uterine AVMs. Study Design Literature databases were searched from 2003 to 2013 for eligible clinical studies, including the patient characteristics, procedural indication, results, complications, as well as descriptions on laterality and embolic agents utilized. Results A total of 40 studies were included comprising of 54 patients (average age of 33.4 years). TCE had a primary success rate with symptomatic control of 61% (31 patients) and secondary success rate of 91% after repeated embolization. When combined with medical therapy, symptom resolution was noted in 48 (85%) patients without more invasive surgical procedures. Conclusion Low-level evidence supports the role of TCE, including in the event of persistent bleeding following initial embolization, for the treatment of acquired uterine AVMs. The variety of embolic agents and laterality of approach delineate the importance of refining procedural protocols in the treatment of the acquired uterine AVM. Condensation A review on the management of patients with acquired uterine AVMs.